Transformation RNA interference-mediated silencing of the Flavanone 3-Hydroxylase gene in Lotus (Nelumbo nucifera Geartn. cv. Buntharik) - Saetiew, K.; Konee, C.; Parinthawong, N.; Arunyanart, S. (International Journal of Agricultural Technology, 2020)
RNA interference mediated-silencing of the F3H gene in the lotus (Nelumbo nucifera Geartn.) cv. Buntharik inhibited the anthocyanin pathway after gene transformation. The plasmid pJA8F3H contained the inverted repeats of F3H fragments, bar gene as a selectable marker in plants, which is resistant to basta (glufosinate amonium). The transformation of particle bombardment was obtained with multiple shoots of lotus. F3H gene expression analysis showed that expression of F3H decreased in transgenic lotus when compared with the control. On the first and the second test, 5 transgenic lotus of the relative expression F3H gene was detected with 0.0496 and 0.466 times, respectively. The inhibition of gene expression decreased when they were cultured for a long time. The expression F3H gene was detected by RT-PCR, and real-time PCR resulted in consistent decreasing in the transgenic lotus compared with the non-transgenic lotus, which was able to inhibit the expression F3H gene.